Assessing rabies-free status of Andaman, Nicobar, and Lakshadweep Islands, India - Shrikrishna Isloor; Reeta S Mani; Mahendra Bangalore Jayakrishnappa (Wolters Kluwer Medknow Publications, 2019)
The Indian Islands of Andaman, Nicobar, and Lakshadweep have been historically rabies-free. However, reliable laboratory evidence to substantiate rabies-free status was lacking. In this background, the study was conducted as a component of the World Health Organization-Association for Prevention and Control of Rabies in India, Indian Multi-Centric Rabies Survey; to assess the rabies-free status of the two Islands and to examine the feasibility of initiating laboratory surveillance for rabies in dogs in Andaman, Nicobar, and Cats in Lakshadweep Islands. A team of medical and veterinary investigators visited these Islands in 2017. A review of 10 years records (2007-2017) in medical and veterinary institutes and interviews with different stakeholders were conducted. Based on the review of records, there was no evidence of human/animal rabies in the Islands. Eight dog brain samples from Andaman, Nicobar Islands, and ten cat brain samples from Lakshadweep Islands were tested negative for rabies by fluorescent antibody test at two rabies diagnostic laboratories at Bengaluru.